Perbandingan Kadar Rheumatoid Factor pada Lansia Obesitas dan Non Obesitas di Komunitas Gla Baiturrohmah - Aini Rifa Putri; Nazula Rahma Shafriani; Arif Bimantara (Yayasan Literasi Sains Indonesia, 2025)
Aging is a biological process that all individuals undergo. Tissues gradually lose their ability to repair and maintain their normal function, leading to various physical or health problems. A common medical issue among older adults is obesity, a condition in which fat accumulates in adipose and can affect a person's health. Hyperinsulinemia, glucose intolerance, dyslipidemia, hypertension, along with rheumatoid arthritis (RA), constitute impacts that obesity can cause. Griya Lansia 'Aisyiyah Baiturrohmah is an elderly community owned by the Regional Leadership of 'Aisyiyah in Yogyakarta which carries out its routine activities two times in a week. This research aimed to compare rheumatoid factor (RF) levels in obese and non-obese elderly and the existence of a link between BMI and RF examination results. This study employed a comparative experimental design with a cross-sectional approach. The study applied complete enumeration, namely all elderly who met the predetermined criteria became research samples, namely 31 people of female gender. The analysis applied both univariate and bivariate techniques within the form of mann-whitney and chi-square tests. No significant difference in RF levels was observed between obese and non-obese elderly individuals (p=0.728). Furthermore, no significant correlation was found between BMI and RF examination results in the elderly within the GLA Baiturrohmah community (p=1.000). The community is expected to maintain an appropriate diet and physical activity because it can help improve blood circulation, muscle strength, and joint stability without putting excessive pressure on the joints.